Is the Sudan Cash Transfer Program Benefiting the Poor? Evidence from the Latest Household Survey - Etang Ndip, Alvin; Hassan, Fareed; Osman, Eiman (World Bank, Washington, DC, 2021)
The objective of this note is to assess the extent to which the CT program is benefiting intended poor households and the appropriateness of the benefit level under the current inflation situation for poverty reduction. This assessment is needed now more than ever as the impending reforms will require having an appropriate system in place for social safety net delivery for the poor and vulnerable. If CT programs are to reach and aid the poor, then ensuring a correlation between poverty and program beneficiaries must be prioritized. Are current beneficiaries of the Sudan CT program, poor households? If targeting is weak, and the answer to the question is no, then scaling up the existing CT program may not achieve its poverty reduction objective. The note proceeds as follows. Section two presents an overview of Sudan’s CT program, including background details, targeting approach used, the number of beneficiaries and the cash transfer amount. Section three shows the extent to which the CT program is benefiting intended poor households based on evidence from the latest household survey data. Section four evaluates the value of the cash transfer, proposing a correct amount required to lift households out of poverty. Section five concludes this note, and additionally, proposes a number of policy recommendations.